Strategi Pengenalan Moral Agama Melalui Kegiatan Jumat Berkah di TK Pertiwi Sowan Kidul - Saputri, Diah Ayu; Afrianingsih, Anita (UIR PRESS, 2025)
Children’s religious moral education is very important from an early age. One way to introduce religious moral values to children from an early age is to carry out Friday blessing activities. The aim of this research is to analyze strategies for introducing religious morals through Friday blessing activities at TK Pertiwi Sowan Kidul. This research uses a qualitative descriptive methodology with a case study approach, collecting information through documentation, interviews, and observation. Data analysis shows an integrative approach to religious moral education and blessed Friday activities, which involves experience-based learning and religious habits, such as congregational prayers and giving alms. The result of this research show that blessed Friday activities such as congregational prayers and alms are an effective way to introduce religious moral values at TK Pertiwi Sowan Kidul. This can help develop children’s religious moral character and produce children who behave well. Children will get use to carrying out daily worship activities as a form of obligation to God. The interview results also revealed that the approach taken by the teacher was able to connect religious moral values with responsibility towards God and others. The challenges faced are bad weather, lack of teacher training, and lack of parental knowledge. This research recommends strengthening teacher training and collaboration between schools and parents. These findings can be a reference in introducing religious moral values through Friday blessing activities with an integrative holistic approach. The conclusion of this research is that children can be introduced to religious morals through Friday blessing activities which are carried out regularly and carried out both in the school environment and at home.